EFFECTIVENESS OF PHYSIOTHERAPY MANAGEMENT OVER QUALITY OF LIFE IN POST OPERATIVE GYNAECOLOGICAL PATIENTS (International Journal of Physiotherapy, 2016)
Background: Gynaecological surgeries refer to surgery on the female reproductive system. Woman may undergo a Gynaecological surgery for different reasons, including; Uterine prolapse, Cancer of the uterus, cervix, or ovaries, Endometriosis, Bleeding, Adenomyosis etc.Gynaecological surgeries includes procedures such as hysterectomy, oopherectomy, salphingectomy, myomectomy, ovarin cystectomy, etc. The Physiotherapy referral is essential in such cases but most of time the patients are not referred for Physiotherapy. Hence the current study was undertaken. Thus the objective is to find out the Effectiveness of Physiotherapy management over quality of life in post-operative Gynaecological patients.Methods: 32 females who underwent Gynecological surgery were taken into the study and divided conveniently into Group A and Group B consisting of 16 females each. Physiotherapy intervention given to Group A includes- Breathing exercises, Coughing techniques, Circulatory exercises, Knee rolling, log rolling, patient made to sit, Abdominal exercises, Pelvic tilting, Getting in and out of the bed, Pelvic floor exercises and mobilization inside the ward, outside the ward and stair climbing where as conventional treatment which includes Breathing exercises and Back care were given to Group B for a period of 5 days. Outcome measures used were VAS (Visual Analog Scale) and ASIS (Abdominal Surgery Impact Scale).Results: There was a significant difference in post test score of VAS (p=0.0001) and ASIS (p=0.0001) in Group A as compared to Group B.Conclusion: This study revealed that physiotherapy intervention performed immediately after Gynecological surgery improves quality of life of the patients and a scheduled exercise program benefits the patient more than conventional Physiotherapy management and it should be emphasized to all the post Gynecological surgery Patients.